User Satisfaction on Academic Information System in UIN KH Abdurrahman Wahid Pekalongan - Alvita Tyas Dwi Aryani; Ahmad Rosyid; Bill Pangayow (Applied Information System and Management (AISM), 2023)
The aim of this research is to evaluate the satisfaction level of students, lecturers, and educational staff towards the integrated academic information system, Sistem Informasi Akademik Terpadu (SIKADU), at UIN KH Abdurrahman Wahid Pekalongan, and to test whether there are any differences in satisfaction levels among these three groups. Additionally, this study aims to identify any issues encountered by users while utilizing it. The population for this research consists of users of SIKADU in UIN KH Abdurrahman Wahid Pekalongan. A convenience sampling technique was employed, and 162 respondents were selected as the sample. The data was analyzed using descriptive statistics, Kruskal Wallis and Cronbach's alpha test. The findings revealed that (1) there are significant differences in satisfaction levels among these three groups (2) 61.8% of the respondents were satisfied with the performance of SIKADU (3) only 17.3% of respondents accessed SIKADU on a daily basis (4) the majority of respondents (67.3%) accessed SIKADU through their mobile phones while at home (5) all dimensions of satisfaction measurement were deemed valid and reliable (6) the primary obstacles faced by the academic community were related to inputting data during course input and downloading scoring forms using SIKADU.